Prevalence of Enterococci and Vancomycin Resistance in the Throat of Non-Hospitalized Individuals Randomly Selected in Central Italy - Palmieri, Annalisa; Martinelli, Marcella; Pellati, Agnese; Carinci, Francesco; Lauritano, Dorina; Arcuri, Claudio; Baggi, Luigi; Gatto, Roberto; Scapoli, Luca (Antibiotics (Basel), 2023)
Enterococci are commonly found in the environment and humans as a part of the normal microbiota. Among these, Enterococcus faecalis and Enterococcus faecium can convert into opportunistic pathogens, making them a major cause of nosocomial infections. The rapid diffusion of vancomycin-resistant strains and their impact on nosocomial settings is of considerable concern. Approximately one-third of the E. faecium infections in Italy are caused by vancomycin-resistant strains. This study explored the hypothesis that the oral cavity could represent a silent reservoir of virulent enterococci. A sample of 862 oral flora specimens collected from healthy human volunteers in Central Italy was investigated by real-time PCR to detect E. faecalis and E. faecium, as well as the genetic elements that most frequently determine vancomycin resistance. The prevalence of E. faecalis was 19%, a value that was not associated with alcohol consumption, tobacco smoking, or age of the subjects. Less frequently detected, with an overall prevalence of 0.7%, E. faecium was more common among people older than 49 years of age. The genes conferring vancomycin resistance were detected in only one sample. The results indicate that the oral cavity can be considered a reservoir of clinically relevant enterococci; however, our data suggest that healthy individuals rarely carry vancomycin-resistant strains.